The Effect Of Exergames On Immune Response Among Secondary School Students In Pulau Pinang, Malaysia - Mohamed, Rwayda Abdulkader (2024)
To the best of our knowledge, no research has been done in Malaysia that investigates the impact of exergames on the immunological response of secondary school students. Therefore, we have conducted two studies to investigate the effect of exergames on the immune response of secondary school students in Malaysia. The first study was divided into two distinct parts. The first phase of the project intended to develop and validate a research instrument in the form of a questionnaire that would specifically measure the knowledge, attitudes, and practice levels of exercise among secondary school students, as well as their experiences with playing exergames. In Phase 2, we utilised the previously validated questionnaire. The first study's findings suggested that our newly developed questionnaire possesses high levels of validity and reliability.